Implementasi Metode Multi Factor Evaluation Process (MFEP) Pada Sistem Penilaian Kinerja Kelurahan di Kecamatan - Siregar, Beni Harianto; Helmiah, Fauriatun; Kifti, Wan Mariatul (Forum Kerjasama Pendidikan Tinggi, 2022)
The Datuk Bandar District Office of Tanjungbalai City annually holds a performance competition between villages to determine the best village by the criteria that have been determined. Selection is carried out through administrative selection, presentation selection, and visit selection, concerning Permendagri number 13 of 2007 concerning guidelines for organizing village and village competitions. For administrative selection, there are already separate rules and systems used to calculate the score of the assessment results. Presentation selection is judged by the mastery of the material, the appearance of giving the material, and the timeliness of the presentation. As for the selection of airy visits, it is assessed from superior products and innovations. So far in the process of assessing the presentation selection and field visit selection at the village competition at the level of the Datuk Bandar District Office of Tanjungbalai City, the assessment team formed by the Tanjungbalai City Datuk Camat still has difficulty in determining the best village performance due to differences of opinion between the assessment team and each other in determining the winner. In addition, the calculation process is still done manually so the calculation results take a long time and the possibility of miscalculation occurs. The results of the village performance competition are considered not objective, it should be worthy of being the best village but not getting it. For this reason, the application of decision support systems is needed to help provide recommendations with more accurate, effective, and efficient results.The method used in this decision support system is MFEP, as an alternative solution for decision-makers to easily determine the village performance competition that deserves the title of the best village based on the weight value obtained in the assessment process. The results of this study, can help in the assessment system of the Village Performance Competition at the Datuk District Office of Tanjungbalai City Where the results of sirantau village as the village with the best performance with a value of 3,765, then sijambi village with a value of 3,471 and johor panti village with a value of 3,412.